How Could We Drink up the Sea? From Technological Nihilism to Dwelling in the Anthropocene (Das Questões, 2021)
Humans face wide ranging and global challenges in the Anthropocene, the most prominent of which is anthropogenic climate change. One initial pivot towards sustainability, particularly in my home country of the United States, has been to rely heavily on technological innovation powered most obviously by engineers. Using the climate activist Greta Thunberg’s speech at the 2018 United Nations Climate Change Conference as my inspiration, I try to show how some of the technology based solutions only entrench what I call the “Bestance” mentality, that is, a fundamental stance or orientation toward the natural world in the Anthropocene wherein all entities show up as mere resources. Upon showing the various ways in which traditional ethical approaches and environmental philosophical approaches have proved unhelpful in navigating the challenges of the Anthropocene, I try to demonstrat e how a Heideggerian ecophenomenological approach can help us not only understand how the world appears to many of us in the Anthropocene, but also what a more graceful way of being might look like in Heidegger’s concept of “dwelling.” Using specific examp les of current technologies pervasively normalized in the United States, including hydraulic fracturing, horizontal drilling, desalination, and artificial nitrogen based fertilization, I use Heidegger’s philosophical concepts to show how the land, sea, and air can show up as Bestand in the Anthropocene, that is, mere materials on hand to be manipulated in order to serve human interests. I then utilize HeideggerHeidegger’s notion of dwelling as a useful concept to guide a more graceful way of living in which we respe ct the way in which things unfold on their own terms using examples similarly embedded in the land, sea and air.